Towards resource-efficient and service-oriented integrated infrastructure operation - Roelich, Katy; Knoeri, Christof; Steinberger, Julia K.; Varga, Liz; Blythe, Phil T.; Butler, David; Gupta, Rajat; Harrison, Gareth P.; Martin, Chris; Purnell, Phil (Elsevier, 2014)
Infrastructure is a means to an end: it is built, maintained and expanded in order to enable the functioning of society. Present infrastructure operation is characterised by: governance based on unmanaged growing demand, which is both inefficient and ultimately unsustainable; lack of integration of the end-users, in terms of the variety of their wants, needs and behaviours; separate and parallel delivery of different infrastructure streams prohibiting joint solutions. To achieve long-term sustainability, infrastructure needs to be designed and operated to provide essential service delivery at radically decreased levels of resource use. This new approach will need to: (1) incorporate the end-user, in terms of their wants and behaviours; (2) focus on the service provided; (3) use Information and Communication Technologies more effectively; (4) integrate the operation of different infrastructure systems; (5) be governed in a manner that recognises the complexity and interconnectedness of infrastructure systems; and (6) rethink current infrastructure valuation. Possible configurations incorporating these aspects with the explicit goal of contributing to long-term sustainability could be Multi-Utility Service Companies or “MUSCos”. This article presents new insights and ideas generated by considering the challenge of the transition towards a MUSCo infrastructure.
Keywords: Sustainable infrastructure operation; Performance economy; Energy Service Company (ESCo); Infrastructure integration; Valuation; Multi-Utility Service Company (MUSCo)